Clinical characteristics and risk factors for mortality in children with Pseudomonas aeruginosa bacteraemia: A retrospective review at a paediatric tertiary centre. (25th June 2021) - Kishimoto, Kenji; Kasai, Masashi; Kawamura, Noriko; Otake, Shogo; Hasegawa, Daiichiro; Kosaka, Yoshiyuki
Abstract : Aim: The objective of this study was to describe clinical features and to assess the risk factors associated with mortality in Pseudomonas aeruginosa bacteraemia in a tertiary Japanese paediatric care hospital. Methods: Patients diagnosed with P. aeruginosa bacteraemia at our hospital between 2007 and 2018 were analysed in a retrospective case series. Inadequate initial therapy for P. aeruginosa bacteraemia was defined as initial treatment without antipseudomonal antibiotics or an administration of antipseudomonal agent to which the causative strain was resistant. Bacteraemia‐related death was defined as all deaths occurring within 7 days after the onset of bacteraemia. Results: Overall, 41 patients with 42 P. aeruginosa bacteraemia episodes were identified. The most common underlying condition was malignancy (27%), followed by congenital heart disease (20%) and preterm birth (17%). Among the 42 P. aeruginosa clinical isolates, 24% were resistant to at least one of the antipseudomonal agents and 10% were resistant to more than one agent. The susceptibility levels for piperacillin, fourth‐generation cephalosporins and ciprofloxacin were higher than that for carbapenems. Bacteraemia‐related death was observed in 43% of episodes. The 30‐day all‐cause mortality was 50% (standard error 8%). Neonates, intensive care, mechanical ventilation, afebrile episodes, septic shock, hypoxia, renal injury and inadequate initial therapy were associated with bacteraemia‐related death episodes. Conclusions: We found that childhood P. aeruginosa bacteraemia is still a high mortality disease. Our results imply the importance of the identification of high‐risk patients and the establishment of adequate empirical antibiotic therapy.